2017
DOI: 10.1093/jme/tjx178
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to House Dust Mites Allergens with Atopic Asthma and Its Relationship with CD14 C(-159T) Polymorphism in Patients of West Bengal, India

Abstract: India is the home to around 15-20 million asthmatics, and asthma prevalence is increasing in Indian metropolitan area, including Kolkata, West Bengal. Complex interactions of genetic and environmental factors are involved in asthma. Genome-wide search for susceptible loci regulating IgE response (atopy) have identified a candidate gene CD14 which is most important in the context of allergic responses of respiratory system. This study was aimed to investigate the role of house dust and house dust mites in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…In our study, we found people who reside in damp houses (whether new or old) were more prone to allergen sensitization. Most of the patients suffered from perennial symptoms over a seasonal pattern that is similar to previous studies [24]. The seasonal pattern of the atopic attacks showed that most of the patients suffered in the dry winter and humid summer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our study, we found people who reside in damp houses (whether new or old) were more prone to allergen sensitization. Most of the patients suffered from perennial symptoms over a seasonal pattern that is similar to previous studies [24]. The seasonal pattern of the atopic attacks showed that most of the patients suffered in the dry winter and humid summer.…”
Section: Discussionsupporting
confidence: 84%
“…The seasonal pattern of the atopic attacks showed that most of the patients suffered in the dry winter and humid summer. In most cases, a perennial pattern was contributed by the inhalation of house dust mite allergens whereas seasonal allergies were caused by molds and pollens [24]. Exposure to the dominant allergens in the air is proved to be associated with increased sensitization in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study from the eastern part (Odisha state) of India in all female subjects has shown an association of rs2569190 (C/T) SNP to increased predisposition to lupus (SLE) and the T-allele frequency was 0.46 for healthy control and 0.58 for SLE cases ( 37 ). The MAF (T allele) in other Indian studies are: West Bengal ( 38 ), 0.53, control vs. 0.49, Asthma case; Chennai ( 39 ), 0.43 in Control vs. 0.54 in Chronic periodontitis case; Hyderabad, Andhra Pradesh ( 40 ), 0.41 in Control vs. 0.53 in Ulcerative Colitis case; Chandigarh ( 41 ), 0.5 in Control vs. 0.64 in NAFLD case; and Lucknow, UP ( 42 ), 0.65 in healthy Control vs. 0.54 in CAD cases. This is a clear indication of an increasing trend of minor T allele frequency from south-eastern to north-Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…510 Symptoms caused by mite sensitization are usually respiratory in nature (sneezing, itching, watery eyes, wheezing, etc). 511 House dust mites constitute an important source of indoor allergens. [510][511][512] Approximately 1% to 2% of the general population worldwide has allergic sensitization towards HDMs which varies between 20% to 80%.…”
Section: Q4 What Are the Source/location Risk Factors And Clinical Si...mentioning
confidence: 99%